2022
DOI: 10.1371/journal.pmed.1003887
|View full text |Cite
|
Sign up to set email alerts
|

Peer-led counselling with problem discussion therapy for adolescents living with HIV in Zimbabwe: A cluster-randomised trial

Abstract: Background Adolescents living with HIV have poor virological suppression and high prevalence of common mental disorders (CMDs). In Zimbabwe, the Zvandiri adolescent peer support programme is effective at improving virological suppression. We assessed the effect of training Zvandiri peer counsellors known as Community Adolescent Treatment Supporters (CATS) in problem-solving therapy (PST) on virological suppression and mental health outcomes. Methods and findings Sixty clinics were randomised 1:1 to either no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 23 publications
(30 reference statements)
2
20
0
Order By: Relevance
“…Two of the three trials examined virologic suppression (this study and the trial among adolescents 44 ), and both failed to demonstrate any statistically significant effect ( eFigure 1 in Supplement 3 ). The present study also examined adherence and equally showed no robust intervention effect.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Two of the three trials examined virologic suppression (this study and the trial among adolescents 44 ), and both failed to demonstrate any statistically significant effect ( eFigure 1 in Supplement 3 ). The present study also examined adherence and equally showed no robust intervention effect.…”
Section: Discussionmentioning
confidence: 89%
“…44 Of note, differences in SSQ-14 and PHQ-9 scores were relatively small, with about 1 score point difference favoring the intervention at 48 weeks. 44…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our multicomponent intervention is based on a combination of evidence-based interventions and recommended but untested strategies to clearly allocate services using a pre-specified algorithm/tool to tailor specific services for AYLHIV. [55][56][57][58][59] Services include individual motivational interviewing to preemptively improve retention, CBT to address depressive symptoms, and enhanced counselling for adherence. System improvements include facility quality improvement and guideline refreshers.…”
Section: Discussionmentioning
confidence: 99%
“…A cluster randomized trial in Zimbabwe evaluated the effectiveness of training community adolescent peer counsellors in problem-solving therapy on mental health outcomes observed improved symptoms of common mental disorder and depression. 52 The effectiveness of peer support programmes as demonstrated in Zimbabwe was so significant such that the country became the first (and perhaps only) to adopt peer support models into its national health system. 53 It is also important that policies are instituted to protect and support pregnant teenagers.…”
Section: Time To Address the Mental Health Of Pregnant Teenagersmentioning
confidence: 99%